1966
DOI: 10.1103/physrev.144.7
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime, Coherence Narrowing, and Hyperfine Structure of the(6s26p7s) P

Abstract: The lifetime and hyperfine structure of the (6s 2 6p7s) IPi 0 excited state in lead have been investigated by the technique of level-crossing spectroscopy. The lifetime of the state was determined to be r=5.75 (20) X10 -9 sec. The linewidth of the level-crossing signal was observed to saturate at a "coherence-narrowed" value in agreement with theoretical predictions. The magnitude of this narrowing corresponds to a 27(3)% branching ratio to the ground state. When the branching ratio and the lifetime are combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1969
1969
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…(1979) for the transitions emitted from eight levels of Pb i excited in a hollow cathode discharge. A set of absolute transition probabilities has been derived for 28 lines using averaged available lifetimes ( Saloman & Happer 1966; Saloman 1966; Savage & Lawrence 1966; Cunningham & Link 1967; DeZafra & Marshall 1968; Garpman et al. 1971; Svanberg 1972).…”
Section: The Oscillator Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1979) for the transitions emitted from eight levels of Pb i excited in a hollow cathode discharge. A set of absolute transition probabilities has been derived for 28 lines using averaged available lifetimes ( Saloman & Happer 1966; Saloman 1966; Savage & Lawrence 1966; Cunningham & Link 1967; DeZafra & Marshall 1968; Garpman et al. 1971; Svanberg 1972).…”
Section: The Oscillator Strengthsmentioning
confidence: 99%
“…Branching ratio measurements have been performed by Lotrian et al (1979) for the transitions emitted from eight levels of Pb i excited in a hollow cathode discharge. A set of absolute transition probabilities has been derived for 28 lines using averaged available lifetimes (Saloman & Happer 1966;Saloman 1966;Savage & Lawrence 1966;Cunningham & Link 1967;DeZafra & Marshall 1968;Garpman et al 1971;Svanberg 1972 (8) 9.80(7) 6p 2 (3/2, 1/2) 2 2628.262 a 23.07 23.08 8.13(5) 7.89(5)* 6p 2 (3/2, 3/2) 2 3671.491 a 20.88 20.89 6.61(7) 6.41(7) 6p 2 (3/2, 3/2) 0 5201.437 a 21.35 21.36 1.09 (7) 1.06 (7) 6p7d Bieron et al (1991), but large discrepancies are observed when comparing length and velocity forms of the dipole operator, indicating a lack of accuracy of the wavefunctions used in the calculations. For most of the transitions common to both works, our results are in between the length and velocity results.…”
Section: T H E O S C I L L At O R S T R E N G T H Smentioning
confidence: 99%
“…tion matrix element has been estimated by Garstang [24]. It leads to a rate of 78 s-1, which is to be compared with the lifetime of 5.75 x 10-' s of the odd parity level (6p 7s) 3P1 [25]. The corresponding ratio 81/M1 ) 1 ils quoted in table I.…”
Section: Circular Dichroism In Molecular Oxygenmentioning
confidence: 99%
“…The level 5d2 is connected not only with the configurations 2p5 4f, 2p5 5p, 2p5 4p, 2p5 3p but with the ground state lSo, too. The possible narrowing of our signal due to the radiation trapping by the last (resonant) channel results in an effective coherence time T2 connected with the radiative time LR in the following way [16] :…”
mentioning
confidence: 99%